Hiatal Surface Area's CT scan measurement is useful in hiatal hernia's treatment of bariatric patients. Issue 2 (1st April 2021) - Boru, Cristian E.; Rengo, Marco; Iossa, Angelo; De Angelis, Francesco; Massaro, Matteo; Spagnoli, Alessandra; Guida, Anna; Laghi, Andrea; Silecchia, Gianfranco
Abstract: Introduction: Hiatal surface area (HSA) measurement has been recently proposed as useful tool for tailored treatment of hiatal defects. Multidetector CT scan (MDCT) of the hiatal area was shown to be useful in hiatal hernia (HH) management. Purpose: MDCT preoperative HSA measurements validation as a useful method in the surgical repair decision making process of hiatal defects in candidates to antireflux ± bariatric surgery. Material and methods: Twenty-five obese patients (group A), candidates to laparoscopic cruroplasty ± bariatric surgery, were prospectively evaluated preoperatively and after one year, using an original MDCT algorithm, compared with intraoperative HSA measurement. Twelve non-obese (group B) and 12 obese patients (group C), without GERD or HH, were used as control groups. Results: Median preoperative HSA was 7.9 cm 2, (interquartile IQR 5.97–9.80) while intraoperative median HSA was 6 cm 2 (6–9.5), p = .84. Postoperative median HSA was 3.8 cm 2 (3.21–4.8), showing the efficacy of cruroplasty, comparable with HSA calculated in the control groups (3.98 for B and 3.69 cm 2 for C, p = .8547). No statistically significant difference between MDCT preoperative measurement and intraoperative findings was observed. Conclusions: Preliminary results demonstrate MDCT scan HSA measurements as a valid, non-invasive method to predict intraoperative findings. It allows the HSA monitoring in order to correlate the symptoms onset and failure of cruroplasty.